2014
DOI: 10.1159/000362207
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Primary Acral Melanomas in Two Young Caucasian Patients

Abstract: Background: Acral melanoma (AM) is still one of the most poorly studied melanomas. It generally presents beyond the fifth decade of life and usually is a BRAF wild-type melanoma. Objective: To report the first cases of multiple primary AM in Caucasians. Methods: Clinical, dermoscopic, pathological and molecular profiles. Results: A healthy 34- year-old male presented an in situ subungual melanoma on his finger, and 22 months later a fast-growing nodular melanoma appeared in an existing nevus on the sole. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…One of the cases presented a subungueal melanoma and a naevus‐associated melanoma on the toe, both BRAF mutated. The findings of our study corroborate the idea that naevus‐associated melanomas located on acral sites would not be related to c‐KIT as de novo acral melanomas, but instead to BRAF , as naevus‐associated melanomas from other sites, such as the trunk …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…One of the cases presented a subungueal melanoma and a naevus‐associated melanoma on the toe, both BRAF mutated. The findings of our study corroborate the idea that naevus‐associated melanomas located on acral sites would not be related to c‐KIT as de novo acral melanomas, but instead to BRAF , as naevus‐associated melanomas from other sites, such as the trunk …”
Section: Discussionsupporting
confidence: 87%
“…In the latter the naevus also harboured mutations in NRAS (D33D and Q61K), not present in the melanoma. Even though it was suggested that most acral melanomas would correspond to de novo melanomas, recently Lacruz et al . described two cases of multiple BRAF ‐mutated acral melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of multiple primary ALMs were reported by Hutcheson et al in 2007 andLacruz et al in 2014 (14, 15). Lacruz et al (15) reported that BRAF mutation was detected in patients with MPM and that it may be a potential risk factor for MPM. The current case did not show BRAF p.V600E mutation in either of the specimens excised in 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data indicate that prominent cutaneous melanoma risk factors (presence of multiple nevi, Caucasian ethnicity, and history of chronic/intermittent sun exposure) are not related to acral melanoma incidence (Nagore et al, 2009). However, multiple acral melanomas in patients at high risk for melanoma such as familial melanoma cases have been reported (Lacruz et al, 2014). A major melanoma risk factor is the presence of multiple common nevi or dysplastic nevi.…”
Section: Cutaneous Melanoma Is a Heterogeneous Group Of Tumorsmentioning
confidence: 99%